The management of persistent pain from a branch of the trifid mandibular canal due to implant impingement - Aljunid, S.; Alsiweedi, S.; Nambiar, Phrabhakaran; Chai, Wen Lin; Ngeow, Wei Cheong (American Academy of Implant Dentistry, 2016)
The mandibular canal is a conduit that allows the inferior alveolar neurovascular bundle to transverse the mandible to supply the dentition, jawbone, and soft tissue around the lower lip. It is now acknowledged that the mandibular canal is not a single canal but an anatomical structure with multiple branches and variations. Iatrogenic injury to branches of the mandibular canal that carry a neurovascular bundle has been reported to cause injury to the main canal as severe as if the main canal itself is traumatized. These injuries include bleeding, neurosensory disturbance, or the formation of traumatic neuroma, and so far, they have involved cases with the bifid mandibular canal. This current report presents a case of neurosensory disturbance that resulted from the impingement of a branch of a trifid mandibular canal during implant insertion. Its management included analgesics, reexamination, and reinserting a shorter implant.